Initial Results of Secukinumab Drug Survival in Patients with Psoriasis: A Multicentre Daily Practice Cohort Study - Juul M.P.A. van den Reek; Lieke J. van Vugt; Martijn B.A. van Doorn; Gayle E. van der Kraaij; Wim J.A. de Kort; Georges P.H. Lucker; Barbara Horvath; M. David Njoo; H. Jorn Bovenschen; Paul M. Ossenkoppele; Marjolein S. De Bruin-Weller; Marjan de Groot; et al. (Medical Journals Sweden, 2018)
Interleukin 17-antagonist secukinumab demonstrated high efficacy for treatment of psoriasis in randomized controlled trials. However, performance in daily practice may differ from trials. Drug survival is a comprehensive outcome covering effectiveness and safety, suitable for analyses of daily practice. The aim of this study was to evaluate drug survival of secukinumab in a daily practice psoriasis cohort. Data were collected from 13 hospitals. Drug survival was analysed using Kaplan-Meier survival curves, split for reason of discontinuation. In total, 196 patients were included (83% biologic experienced). Overall, 12 and 18 months drug survival of secukinumab was 76% and 67%, respectively, and was mostly determined by ineffectiveness. There was a trend towards shorter drug survival in women and in biologic experienced patients. Thirteen percent of patients experienced at least one episode of fungal infection. This is one of the first studies of drug survival of secukinumab in patients with psoriasis treated in daily practice.